Auditoría tributaria preventiva y su incidencia en el riesgo tributario de la empresa T- Soluciona S.A.C., distrito de Trujillo- 2017. - Méndez Gutierrez, Xiomara Milagritos (2019)
ABSTRACT The purpose of the investigation was to determine the incidence of the preventive tax audit on the tax risk of the company T-Soluciona SAC, District of Trujillo -2017, with the purpose of contributing to the development of the accounting-tax area of the company and to avoid possible contingencies before the tax administration. The study method used is descriptive, analytical, the design of non-experimental study, the population are all companies dedicated to the administration of payroll, selection and evaluation of personnel, process outsourcing and data verification of the District of Trujillo, consisting of 15 companies and the sample is the company T- Soluciona SAC, as well as the techniques used to obtain the information in the documentary analysis, the application of surveys and interviews. The results are converted into the results in the tables and the figures are determined compliance with tax obligations and the identification of the level of tax risk. It is concluded that the incidence of the preventive tax audit on the tax risk of the company T- Soluciona S.A.C., District of Trujillo- 2017, is positive. It was determined that the company incurred payments due to SUNAT for an amount of S / 80,844.53, in addition to fines and repairable expenses for an amount of S / 41,925.27, which can be reduced to S / 1,566.55 by applying graduality. It is recommended that the present investigation be the beginning, on which the general review of the company can be built, it is considered that tax control practices should be developed and the first steps to take the necessary measures to reduce the amount of Findings before a possible inspection.